(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Keloid is a benign fibro-proliferative disorder characterized by excessive collagen deposition extending beyond the original wound margins. Although commonly observed after ear piercing, burns, and surgeries over the chest and shoulders, its occurrence following inguinal herniotomy is rare, particularly in the paediatric age group. We report a case of a 12-year-old boy who developed a progressively enlarging keloid over a right inguinal surgical scar following herniotomy performed one and half year back for congenital inguinal hernia. The lesion was cosmetically disfiguring and resistant to conservative management. This case emphasizes the need for awareness of abnormal scar responses even in low-tension surgical areas and highlights the importance of multimodal management and long-term follow-up.